Konseptualisasi Pembangunan Komuniti melalui Analisis Konsep Struktur Sosial, Teori Modal Sosial dan Perspektif Realisme Kritikal (Jurnal Pembangunan Sosial, 2015)
This article discusses the conceptualization of community development through sociological analysis of the concept of social structure and social capital through the lenses of critical realism. The main goal of the discussion is to develop a novel conceptual framework of community development using the typical setting of a Malay community that practices the Islamic way of life as the basis. Social capital theory, structuration theory and critical realism philosophical perspective were utilized as the theoretical basis for the development of the framework. The concept of social capital regards the community as incubators for resources deemed crucial for individual and community well-being. The harnessing of these resources in the form of social capital is considered an important factor in the overall process of community development. perspective provide the theoretical basis capable of delineating the processes and mechanisms involved in the production of social capital and thereby increase the community functioning. The resulting conceptual framework provides a non-conventional view of the process of community development and provides better understanding of the role of religious institutions such as the community mosque. Additionally, structuration theory and critical realism